Prevalence of Hepatitis B and C among HIV Infected Patients in Nepal over 1990-2020 - Shrestha, D. B.; Budhathoki, P.; Sedhai, Y. R.; Shrestha, L. B.; Awal, S.; Upadhaya Regmi, B.; Yadav, J.; Baniya, R.; Thapaliya, S.; Dangal, G. (Kathmandu University Medical Journal, 2021)
Background Hepatitis B and C (HBV and HCV) are viral infections caused by corresponding viruses. Here in this study we planned to conduct this meta-analysis to pool data on the prevalence and risk factors of HBV and/or HCV among HIV patients in Nepal.Method We used MOOSE guideline for the systemic review of available literature. We searched online databases using appropriate keywords. We used CMA-3 for data synthesis. Odds ratio, and proportion were used to estimate the outcome with a 95% confidence interval where appropriate. We assessed the heterogeneity using the I-squared (I2) test.Result We included nine studies for our synthesis. Pooling of data showed HBV in 4.6% (CI: 3.7-5.6), HCV in 19.7% (CI: 10.8-33.0), both HBV and HCV in 1.3% (CI: 0.5-3.7) in HIV affected individuals. Among HBV co-infected HIV positive patients, 59.5% (CI: 25.5-86.3) were male; 76.1% (CI: 30.1-96.0) were married and 43.6% (CI: 3.8-93.8) had a history of intravenous drug use (IVDU). Among HCV co-infected HIV positive individuals 88.3% (CI: 73.6-95.4) were male; 63.6% (CI: 55.4-71.1) were married; 91.5% (CI: 68.6-98.1) were literate; 59.2% (CI: 49.9-67.9) were on ART; and 92.2% (95%CI: 84.9-96.1) had a history of IVDU.Conclusion The pooled prevalence of co-infection with HBV, HCV, and combined HBV and HCV were 4.6%, 19.7% and 1.3% respectively among HIV positive patients. Thus, it is necessary to appropriately screen for HBV and HCV in individuals diagnosed with HIV and high-risk populations. IVDU remains the most common risk factor found in co-infected individuals.